Guide to intra-state wars : an examination of civil wars, 1816-2014 - Dixon, Jeffrey S. (CQ Press/SAGE Reference, 2015)
Sourcing data and analyses from the rigorous Correlates of War Project, A Guide to Intra-state Wars describes how civil war is defined and categorized and presents data and descriptions for nearly 300 civil wars waged from 1816 to 2014. Analyzing trends over time and regions, this work is the definitive source for understanding the phenomenon of civil war, bringing together an explanation of the theoretical premises driving the Correlates of War Project, along with revisions to categories of, and actors in, civil wars that have been made over the years, and data from the Nations, States and En.